2016
DOI: 10.1007/s13199-016-0464-1
|View full text |Cite
|
Sign up to set email alerts
|

Cymbomonas tetramitiformis - a peculiar prasinophyte with a taste for bacteria sheds light on plastid evolution

Abstract: Cymbomonas tetramitiformis is a peculiar green alga that unites in one cell the abilities of photosynthesis and phagocytosis, which makes it a very useful model for the study of the evolution of plastid endosymbiosis. We have pondered over this issue and propose an evolutionary scenario of trophic strategies in eukaryotes, including primary and secondary plastid endosymbioses. C. tetramitiformis is a prototroph, just like the common ancestor of Archaeplastida was, and can synthesize most small organic molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Most of the studies on the endophytes were focused on non-woody crops, moreover most of them used culture-dependent methods ( Shen and Fulthorpe, 2015 ; Szymańska et al, 2016 ). Data on bacterial and fungal endophytes in roots of forest trees under saline stress are very limited ( Ju et al, 2014 ; Hrynkiewicz et al, 2015 ; Thiem et al, 2017 ), and our work is the first report describing application of metagenomics to such a community with particular emphasis on root symbionts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies on the endophytes were focused on non-woody crops, moreover most of them used culture-dependent methods ( Shen and Fulthorpe, 2015 ; Szymańska et al, 2016 ). Data on bacterial and fungal endophytes in roots of forest trees under saline stress are very limited ( Ju et al, 2014 ; Hrynkiewicz et al, 2015 ; Thiem et al, 2017 ), and our work is the first report describing application of metagenomics to such a community with particular emphasis on root symbionts.…”
Section: Discussionmentioning
confidence: 99%
“…The study was carried out in mid-northern Poland at two test sites: a non-saline one in Pszczółczyn (53° 00′22.9″ N, 17° 54′57.2″ E; NS) and a saline one in Słonawy (53° 01′26.6″ N, 17° 37′47.3″ E; S) ( Thiem et al, 2017 ). Salinity of soils in this area results from the impact of saline springs contacting with the Zechstein (Permian) salt deposits ( Dadlez and Jaroszewski, 1994 ).…”
Section: Methodsmentioning
confidence: 99%
“…This transfer was probably accompanied by transfers from bacterial sources (for example Z ahonov a et al, 2018). Unexpectedly, the analysis of nuclear genes of algal origin in eukaryotic lineages Gagat & Mackiewicz (2017) with complex plastids has revealed a wide range of putative algal donors that are different from the algal endosymbionts that exist today as secondary plastids (Curtis et al, 2012). For instance, despite diatoms containing plastids clearly derived from red algae, phylogenetic analysis of diatom nuclear genomes has suggested that > 1700 nucleus-encoded genes were apparently transferred from green algae (Moustafa et al, 2009).…”
Section: Complex Plastidsmentioning
confidence: 99%
“…B. paralicheniformis is a Gram-positive species of the Bacillus genus. Rubén Palacio-Rodríguez et al reported that B. paralicheniformis LBEndo1 can promote the growth of Arabidopsis thaliana ( 5 ). B. paralicheniformis MDJK30 was isolated from the rhizosphere of peony in Shandong, China.…”
Section: Genome Announcementmentioning
confidence: 99%